The Role of Student Management in Developing Students' Potential and Character at SDN 111/1 Muara Bulian - Aulia fitriana Adrian (MISOOL: Jurnal Pendidikan Dasar, 2026)
Student management is a crucial aspect of elementary education because it helps students build character and optimize their abilities. This study aims to examine how student management at SDN 111/I Muara Bulian can improve their skills and character traits. Previous research serves as the foundation for this study, which examines elements such as parental involvement, support services, potential development, character development, and various differences among students in classroom management. This study involves students, the principal, and teachers as research subjects and focuses on student administrative management. It employs a descriptive approach with a qualitative methodology. Data were collected through observation, interviews, and documentation, and analyzed using data condensation, data display, and conclusion drawing.  The results indicate that there are several ways to support student learning, including academic and non-academic programs, individual development, active collaboration between students and the school, and character development. Character, talents, interests, and learning needs are key issues that require attention. According to the findings, students who are cooperative, adaptable, and well-organized can develop their potential and cultivate their character in the classroom.